Surgical Treatment and Rehabilitation of Children with Pathology of the Pancreas - Yu.V. Pashchenko; О.Yu. Belousova; V.A. Belopashentsev (Zaslavsky O.Yu., 2016)
Relevance. Surgical treatment of pancreas pathology in children is quite difficult in pediatric surgery. The diversity of pathology in congenital anomalies in the glands structure, complications, ectopic tissue of pancreas have often been related to difficulties in choice of the complex invasive method of diagnosis and treatment for surgeons. Research objective: to create optimal treatment approaches to organ and extraorgan pancreas pathology management in children. Materials and methods. We have practiced in treatment of 50 children with malformations and diseases of the pancreas aged from 2 months to 17 years old. Extraorgan pancreatic tissue ectopias (25), destructive pancreatitis (10), reactive cysts (8), traumatic injuries (3), lymphangioma (1), aggressive fibrosis (1), teratoma (1), an insulinoma (1) were registered. The diagnostic methods included clinical laboratory methods, EGD, radiation methods. Results. We described the surgical interventions in children using minimal access, laparoscopic technology, stenting and open surgery. The article explains principles of standard treatment with concomitant medications and diet in the postoperative period. Conclusions. The experience of the treatment of congenital and acquired pancreas pathology showed the effectiveness for proposed approaches and potential of mini-invasive technologies development in surgical correction. We have developed the basic principle of treatment and rehabilitation of patients by gastroenterologist - pediatric surgeon - gastroenterologist which allows achieve a high level of good and satisfactory results of treatment in children. We have formed and implemented into the practice the algorithm of actions for internists and pediatric surgeons at different stages of the disease.